Public administration of employment of the population of rural territories under the conditions of marital state and post-war reconstruction - Babaiev, Valerij; Babaieva, Iryna (Pressing Problems of Public Administration, 2022)
The scientific study highlights the general situation that has developed under martial law, namely mass migration of the population, reduction of the economically active population, reduction of labor and educational potential, significant civilian casualties, and an increase in the number of people with disabilities and psycho-emotional disorders. Attention is focused on the importance of the effectiveness of public policy in solving issues of promoting employment of the population, creating jobs, promoting self-employment and the development of entrepreneurship. The activities of local self-government bodies, namely, united territorial communities, regarding the solution of urgent issues regarding their functioning in new conditions, and especially meeting the needs of the army, accommodation of relocated enterprises, life support for internally displaced persons, formation and distribution of humanitarian aid, etc., were considered. The need to replace the passive measures of the state employment policy with active ones has been proven, namely, assistance in promoting employment through retraining, opening one’s own business, training, etc. It is substantiated that the development of employment in rural areas is possible through the support of non-agricultural activities, provided that there are no other agricultural areas of employment in the settlement. The advantages and disadvantages of the government program for the relocation of enterprises, the “eRobota” project, are considered, and the attention is focused on the effects of these programs both for the territory of the country as a whole and for rural territorial communities in particular. A method of solving the problem of agrarians regarding the disruption of logistics processes and transport connections by creating agro-logistics hubs is given. It is proposed to create multifunctional cooperative and communal procurement and sales points to support rural entrepreneurship and self-employment.